INNOVATIVE DEVELOPMENT OF MANUFACTURING ENTERPRISES: TRENDS AND PROSPECTS - A. V. Platonova (Publishing House of the State University of Management, 2020)
The author’s method of evaluating the innovative development of manufacturing enterprises has been presented. Three key stages of evaluation activities have been highlighted. At the first stage, the leading group of manufacturing enterprises in terms of innovative development was identified – high-tech enterprises. At the second stage attention was paid to the rating innovative development of high-tech enterprises based on the authorial structural grouping of innovation indicators. At the third stage high-tech enterprises allocation to positions of innovative development (innovative leader, developed or developing innovator) and sectors of innovative development (balanced, result- or potential- oriented) has been proposed.